Combustion, performances, and emissions characteristics of diesel engine fuelled with diesel-aqueous zinc oxide nanofluid blends. Issue 1 (31st December 2023) - Venkatesan, Sorakka Ponnappan; Kadiresh, Parthasarathy Natarajan; Beemkumar, Nagappan; Jeevahan, Jeya
ABSTRACT: Finding the new fuel blend as a green fuel by mixing aqueous zinc oxide nanofluid with diesel to improve diesel engine combustion and performance is the aim of this study. Varying the nanofliud dosing level in diesel from 30 cc to 60 cc, four blends are prepared and their properties are measured. Engine performance tests are conducted with the blends and the best blend is identified as D + 50ZN. The energetic nanoparticles present in the aqueous nanofluid possess large surface area per unit volume, it exhibits high catalytic activity with hydrocarbon causing oxidation of hydrocarbon and also micro explosion phenomena of aqueous nanofluid blend helps to evaporate the blend quickly as soon as the fuel injected from injector with high speed and some millimeters away from the normal spay limit leading to quick preparation of charge during the delay period. Hence, the fuel is completely burnt during the combustion period. Among all blends, The D + 50ZN showed a maximum improvement of about 5.38% in brake thermal efficiency and remarkable reduction in NOX, smoke, HC, and CO is observed as 12.97%, 22.08%, 24.54%, and 10.34%, respectively at maximum rated power output. Abbreviation: ASTM: American Society for Testing and Materials; aTDC: After Top Dead Center; BP: Brake Power; BSFC: Brake Specific Fuel Consumption; bTDC: Before Top Dead Center; BTE: Brake Thermal Efficiency; CO: Carbon Monoxide; DDSA: Dodecenyl Succinic Anhydride; EDS: Energy Dispersive Spectroscopy; HC: Hydrocarbons; JCPDS: Joint Committee on Powder Diffraction Standards; NOX: Oxides of Nitrogen; ppm: Part Per Million; SEM: Scanning Electron Microscope; XRD: X-Ray Diffraction Pattern; ZN: Aqueous Zinc Oxide Nanofluid; ZnO: Zinc Oxide